2010
DOI: 10.1098/rsta.2010.0031
|View full text |Cite
|
Sign up to set email alerts
|

Response of faults to climate-driven changes in ice and water volumes on Earth’s surface

Abstract: Numerical models including one or more faults in a rheologically stratified lithosphere show that climate-induced variations in ice and water volumes on Earth's surface considerably affect the slip evolution of both thrust and normal faults. In general, the slip rate and hence the seismicity of a fault decreases during loading and increases during unloading. Here, we present several case studies to show that a postglacial slip rate increase occurred on faults worldwide in regions where ice caps and lakes decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Factors such as rebound or decompression (elastic recovery) from flexure or compression of the lithosphere by ice masses, past glacial erosion or redistribution of sediment overburden, porewater pressure changes, sea-level changes, and release of locked-in stresses or elastically stored tectonic stresses have been discussed (Mörner, 1978;Gudmundsson, 1994;Mörner, 1995;Arvidsson, 1996;Beck et al, 1996;Firth and Stewart, 2000;Fjeldskaar et al, 2000;Muir-Wood, 2000;Stewart et al, 2000;Wu and Johnston, 2000;Zoback and Grollimund, 2001;Karrow and White, 2002;Persaud and Pfiffner, 2004;Becker et al, 2005;Wu and Mazzotti, 2007;Lagerbäck and Sundh, 2008;Turpeinen et al, 2008;Gregersen and Voss, 2009;Bungum et al, 2010;Calais et al, 2010;Hampel et al, 2010;Wu et al, 2010). Despite some ongoing debates, it seems likely that the large-scale unloading of continental ice masses is sufficient to generate, enhance, or trigger seismicity on a regional scale.…”
Section: Seismicitymentioning
confidence: 99%
“…Factors such as rebound or decompression (elastic recovery) from flexure or compression of the lithosphere by ice masses, past glacial erosion or redistribution of sediment overburden, porewater pressure changes, sea-level changes, and release of locked-in stresses or elastically stored tectonic stresses have been discussed (Mörner, 1978;Gudmundsson, 1994;Mörner, 1995;Arvidsson, 1996;Beck et al, 1996;Firth and Stewart, 2000;Fjeldskaar et al, 2000;Muir-Wood, 2000;Stewart et al, 2000;Wu and Johnston, 2000;Zoback and Grollimund, 2001;Karrow and White, 2002;Persaud and Pfiffner, 2004;Becker et al, 2005;Wu and Mazzotti, 2007;Lagerbäck and Sundh, 2008;Turpeinen et al, 2008;Gregersen and Voss, 2009;Bungum et al, 2010;Calais et al, 2010;Hampel et al, 2010;Wu et al, 2010). Despite some ongoing debates, it seems likely that the large-scale unloading of continental ice masses is sufficient to generate, enhance, or trigger seismicity on a regional scale.…”
Section: Seismicitymentioning
confidence: 99%
“…In particular, I focused on climate-related surface processes involving the redistribution of large masses (ice and water). Various papers have shown that despite the weak stress changes they can cause at depth compared to the tectonic stress, they are potentially able to control seismicity at different time scales: from seasonal (Bettinelli et al 2008) to millennial (Luttrell and Sandwell 2010;Hampel et al 2010). Furthermore, some climate processes have a periodicity similar to that of the earthquakes (Scafetta and Mazzarella 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that variations of the global temperature cause the movement of large masses, through atmospheric and oceanic circulation, sea-level rise, ice and snow melting, and inland water accumulation due to intense rainfall. Geophysical models, such as those by Hampel et al (2010) and Luttrell and Sandwell (2010), demonstrate that the consequent change of the surface load could control faulting, either promoting or inhibiting earthquakes. Furthermore, similar processes seem to act on different time scales, going from seasonal to millennial [see (Bragato 2015) for a short review on the subject].…”
Section: Discussionmentioning
confidence: 99%
“…In the final discussion, I simply address the question with reference to the available literature. In particular, I observe a strict anticorrelation with the global surface temperature and, following authors, such as Hampel et al (2010) and Luttrell and Sandwell (2010), hypothesize a possible role of the sea-level changes.…”
Section: Introductionmentioning
confidence: 99%